Rethinking clusters. Towards a new research agenda for cluster research. Issue 10 (3rd October 2019) - Lazzeretti, L.; Capone, F.; Caloffi, A.; Sedita, S. R.
ABSTRACT: Notwithstanding the wide research on clusters and industrial districts, most of the preceding contributions tried to analyse and investigate past research and rarely tried to critique or propose any future trajectories of this stream of research. The aim of this special issue is to identify and discuss the main themes of research that populate the current scientific debate and highlight the emergent lines that may well set the future research agenda. In order to provide a scenario for better understanding the content of this special issue, in this work, we encouraged a mix of quantitative and qualitative approaches. In particular, to identify the most important themes of current and future research, we present a bibliometric analysis of the papers that were presented at the international workshop 'Rethinking Clusters', which took place in Florence in 2018, with more than 100 participants. This exercise together with a wider literature review permits us to propose a new research agenda on cluster research according to eight main themes. These range from cluster life cycles, through creativity, innovation, knowledge networks, cluster policy issues, internationalization, sustainability, finally to cluster variety and relatedness.